Hi Art,
Using the distributive law as you describe I get
30+7(x1)=3(2x+7) so
30 + 7x  7 = 6x + 21
At this point I see two types of terms, those that involve x and those that don't involve x. On each side of the equation collect the terms that involve x and the terms that don't involve x. I get
30 + 7x  7 = 6x + 21 so
30 7 + 7x = 6x + 21 and thus
23 + 7x = 6x + 21
At this point I would collect all the terms that involve x on one side of the equation and all the terms that don't involve x on the other side, To do this first add 6x to both sides.
23 + 7x = 6x + 21 and hence
23 + 7x 6x = 6x + 21 6x and thus
23 + x = 21
Finally add 23 to each side to get
23 + x  23 = 21  23 and hence
x = 2
I hope this helps,
Penny
